2015
DOI: 10.1136/jech-2014-204248
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of health behaviours and socioeconomic differences in mortality in the USA

Abstract: Background To measure the explanatory role of behavioral factors to educational and income disparities in mortality among U.S. adults (ages 25+). Methods Data were from 4 waves of the American Changing Lives Study (N=3,617). There were 1,832 deaths between 1986 and 2011. Smoking, physical activity, alcohol, and BMI were examined. Results Those with 0–11 years of schooling had an 88% (95% CI: 48%, 139%) increased risk of dying compared to those with 16+ years of schooling. Behavioral factors explained 41% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 40 publications
4
23
2
Order By: Relevance
“…Moreover, these studies suggest a tendency that the contribution of health behaviours is larger when longitudinal data of health behaviours are used 8 11 13. We have argued that several mechanisms may be responsible for differences between time-fixed and time-varying models and that the extent to which they do so may vary by health behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these studies suggest a tendency that the contribution of health behaviours is larger when longitudinal data of health behaviours are used 8 11 13. We have argued that several mechanisms may be responsible for differences between time-fixed and time-varying models and that the extent to which they do so may vary by health behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the role of physical activity in the explanation of socioeconomic inequalities in mortality has been shown to increase when multiple measurements of physical activity are used, even in the presence of a declining socioeconomic gradient in physical activity 8. Also, while inequalities in smoking increased over time, some studies have found no difference in the contribution of smoking between time-fixed and time-varying models 8 11. We argue that several mechanisms may cause differences in results between time-fixed and time-varying models, and that the extent to which they do so may vary by mediator.…”
Section: Introductionmentioning
confidence: 99%
“…25,27 This interpretation is supported by studies showing that health behavior has a larger role in explaining educational disparities compared with income disparities. 28 …”
Section: Discussionmentioning
confidence: 99%
“…It is also central to answering the common question of how much of sociodemographic differences in mortality are “explained by” differences in smoking, obesity, and other behavioral factors. The answer to this question is normally a function of differences in the distribution of behavioral factors across socioeconomic groups (e.g., Mehta et al, 2015; Nandi et al, 2014). However, differences in the responsiveness of various groups to behavioral factors should also be assessed in such an inquiry.…”
Section: Discussionmentioning
confidence: 99%